The temporal and spatial variation of chlorophyll a concentration in the China Seas and its impact on marine fisheries - Kunlong Zhang; Xunbo Zhao; Jing Xue; Danqi Mo; Dongyu Zhang; Zhongyong Xiao; Wei Yang; Yingxu Wu; Yingfeng Chen (Frontiers in Marine Science, 2023)
Marine chlorophyll a is a key molecule for photosynthesis of marine plants and some plankton, which is important in marine ecosystems. This study utilized the chlorophyll a concentration data product observed by the MODIS sensor (MODerate resolution Imaging Spectroradiometer) to construct a long-term sequence of chlorophyll a concentration dataset by processing the raw data. Based on this, the multi-time-scale chlorophyll a concentration data was synthesized, and it was used to analyze the spatial and temporal variation characteristics of chlorophyll a concentration in China Seas. In addition, several oceanographic variables, including sea surface temperature, nutrients (phosphate, nitrate, silicate), partial pressure of seawater carbon dioxide, net primary productivity of the ocean, physical dynamics of seawater processes (mixed layer), were analyzed to ascertain their potential influence on chlorophyll a concentration. Finally, we analyzed the effects of changes in chlorophyll a concentration on marine fisheries. The result showed that: The average value of chlorophyll a concentration in China Seas from 2002 to 2022 was 0.874 mg/m 3 , with the highest concentration observed in the Bohai Sea area (4.547 mg/m 3 ) and the lowest in the South China Sea area (0.288 mg/m 3 ). The spatial variation of chlorophyll a concentration revealed an overall decrease of 0.0095 mg/m 3 in China Seas from 2002 to 2022. From the perspective of time changes, the concentration of chlorophyll a in China’s Bohai Sea area showed a downward trend from 2002 to 2022, while the Yellow Sea area showed an upward trend. The concentration remained relatively stable in the East China Sea area, whereas a significant declining trend was observed in the South China Sea area. The relationship between temperature and chlorophyll a concentration was non-linear, and chlorophyll a concentration showed some fluctuation or threshold effect with the change of seawater temperature. The three nutrient salts studied have a promoting effect on chlorophyll a, among which phosphate has the most obvious promoting effect on chlorophyll a. Chlorophyll a was negatively correlated with pCO 2 and positively correlated with ocean net primary productivity. Seasonal changes in the mixed layer had a significant effect on changes in the upper marine nutrients, which in turn affected changes in chlorophyll a concentration. Six of the eight types of algae studied show a trend toward deeper sea depths, which may have implications for the food availability of marine fish at different levels and pose new challenges for marine fisheries development.